Application of Small Punch Test Method in Studies of the 14MoV63 Steel Before and After Revitalisation - Kłaput J. (Archives of Metallurgy and Materials, 2015)
The paper presents the results of studies of the chromium-molybdenum-vanadium steel designed for operation at elevated temperatures. The material was examined after long-term operation and after the revitalising heat treatment. Studies were performed by conventional methods and small punch test. Curves of ductile-brittle transition were plotted from the Charpy V-notch impact tests and were next compared with the curves of sudden loss of ductility obtained in the small punch test. Additionally, for the material before and after revitalisation, the values of temperatures Tpk and Tnuc were calculated using the method of inflection point.